Rfid Door Lock With Realization Of Internet Of Things For Smart Home System - Zafirah, Zainon (Universiti Sains Malaysia, 2017)
Home is the most comfort place for us. Therefore, a home security system is very crucial for us to live freely and happily. This smart door lock with RFID and IoT implementation is developed to bring convenience, utility and security altogether. Nowadays, the wireless communication are more towards low cost and low power consumption. Therefore, this project is designed for low cost smart home implementation as it is more affordable to the society. This system made easier for home occupant to track record of check-in and check-out of the house. There are two important parts in this project that need to be developed which are user friendly smart door lock system and main controller module. The smart door lock will require Wi-Fi access to communicate with the home occupant emails’. The system will be controlled using the Arduino Uno microcontroller board. RFID tag or card will be sensed by the RFID reader, then the data is transmitted to the home occupant emails’. If the RFID tag or card bypass the reader, the reader will grant access and the servo will turn 90° to unlock the door. However, if the detected tag or card is not being approved by the reader, it will deny the access and stay initially static.